"Bubble-in-the-Roll" Technique Using the Endoject DMEK Injector: Influence of the Air Bubble on Endothelial Cell Loss. Issue 12 (December 2017) - Akbaba, Yasemin; Weller, Julia M.; Rössler, Kathrin; Armitage, W. John; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich E.; Tourtas, Theofilos
Abstract : Purpose: To evaluate the impact of the air bubble on endothelial cell loss using the "bubble-in-the-roll" technique during Descemet membrane endothelial keratoplasty (DMEK). Methods: Twenty DMEK grafts not suitable for transplantation were manually prepared from organ-cultured corneoscleral discs and injected into culture media using the Endoject DMEK injector (Medicel AG, Wolfhalden, Switzerland). Based on the injection method, the grafts were divided into 2 groups: In group A (n = 10), a small air bubble was placed inside the graft roll while it was in the injector. In group B (n = 10), the grafts were injected without an air bubble inside the graft roll. Main outcome measures included endothelial cell density (ECD) after graft stripping and graft injection. Results: There were no statistically significant differences between groups A and B in donor age, storage duration, and donor ECD. ECD decreased from 1929 ± 145 cells/mm 2 to 1796 ± 303 cells/mm 2 after graft stripping in group A and from 1801 ± 226 cells/mm 2 to 1709 ± 290 cells/mm 2 in group B. ECD after graft injection further decreased to 1683 ± 291 cells/mm 2 in group A and to 1651 ± 292 cells/mm 2 in group B. Endothelial cell loss after graft stripping and graft injection was not statistically significant between groups A and B ( P = 0.29 and P = 1, respectively). Conclusions: The bubble-in-the-roll technique for injection and unfolding of the graft is a safe method for graft delivery into the anterior chamber guaranteeing orientation of the graft without harming the endothelium. Abstract : Supplemental Digital Content is Available in the Text.